Wrongful Convictions and Prosecutions in Latin America: A Systematic Literature Review (2010-2023) - Duce, Mauricio; Beltrán, Víctor (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2024)
Drawing on a systematic literature review, this paper examines the scholarly discourse surrounding wrongful convictions and prosecutions in Latin America, spanning from 2010 to July 2023, across the WoS, Scopus, and SciELO databases, identifying a set of 50 publications. From a quantitative perspective, the paper inquiries into aspects such as publication year, countries covered, characteristics of the scientific community involved, and the topics addressed. Then, the paper briefly delves into a qualitative analysis of the publications’ content, distinguishing among those that address general aspects, factors contributing to wrongful convictions and prosecutions, correction mechanisms, and compensation mechanisms for wrongful convictions and prosecutions. Although with limitations, the findings provide an overview of research in this area in Latin America, showing that, although scholarship is still scarce compared with other latitudes, the topic has begun to attract interest in recent years in the region.